Evidence for disrupted gray matter structural connectivity in posttraumatic stress disorder. Issue 2 (30th November 2015) - Mueller, Susanne G.; Ng, Peter; Neylan, Thomas; Mackin, Scott; Wolkowitz, Owen; Mellon, Synthia; Yan, Xiaodan; Flory, Janine; Yehuda, Rachel; Marmar, Charles R.; Weiner, Michael W.
Abstract: Posttraumatic stress disorder (PTSD) is characterized by atrophy within the prefrontal–limbic network. Graph analysis was used to investigate to what degree atrophy in PTSD is associated with impaired structural connectivity within prefrontal limbic network (restricted) and how this affects the integration of the prefrontal limbic network with the rest of the brain (whole-brain). 85 male veterans (45 PTSD neg, 40 PTSD pos) underwent volumetric MRI on a 3T MR. Subfield volumes were obtained using a manual labeling scheme and cortical thickness measurements and subcortical volumes from FreeSurfer. Regression analysis was used to identify regions with volume loss. Graph analytical Toolbox (GAT) was used for graph-analysis. PTSD pos had a thinner rostral anterior cingulate and insular cortex but no hippocampal volume loss. PTSD was characterized by decreased nodal degree (orbitofrontal, anterior cingulate) and clustering coefficients (thalamus) but increased nodal betweenness (insula, orbitofrontal) and a reduced small world index in the whole brain analysis and by orbitofrontal and insular nodes with increased nodal degree, clustering coefficient and nodal betweenness in the restricted analysis. PTSD associated atrophy in the prefrontal–limbic network results in an increased structural connectivity within that network that negatively affected its integration with the rest of the brain. Highlights: Prefrontal–limbic functional and structural abnormalities characterize PTSD. Cortical thickness measurements were obtained from 85 veteran with and without PTSD. Prefrontal limbic structural connectivity was characterized using graph analysis. Integration of the prefrontal–limbic network with the rest of the brain is impaired. PTSD is associated with a loss of the economical small world topology.